Mechanisms Involved in Nicotinic Acetylcholine Receptor-Induced Neurotransmitter Release from Sympathetic Nerve Terminals in the Mouse Vas Deferens - Williams, Damian J.; Sidaway, Peter; Cunnane, Thomas C.; Brain, Keith L. (PLOS ONE, 2011)
Prejunctional nicotinic acetylcholine receptors (nAChRs) amplify postganglionic sympathetic neurotransmission, and there are indications that intraterminal Ca2+ stores might be involved. However, the mechanisms by which nAChR activation stimulates neurotransmitter release at such junctions is unknown. Rapid local delivery (picospritzing) of the nAChR agonist epibatidine was combined with intracellular sharp microelectrode recording to monitor spontaneous and field-stimulation-evoked neurotransmitter release from sympathetic nerve terminals in the mouse isolated vas deferens. Locally applied epibatidine (1 µM) produced ‘epibatidine-induced depolarisations’ (EIDs) that were similar in shape to spontaneous excitatory junction potentials (SEJPs) and were abolished by nonselective nAChR antagonists and the purinergic desensitizing agonist α,β-methylene ATP. The amplitude distribution of EIDs was only slightly shifted towards lower amplitudes by the selective α7 nAChR antagonists α-bungarotoxin and methyllcaconitine, the voltage-gated Na+ channel blocker tetrodotoxin or by blocking voltage-gated Ca2+ channels with Cd2+. Lowering the extracellular Ca2+ concentration reduced the frequency of EIDs by 69%, but more surprisingly, the Ca2+-induced Ca2+ release blocker ryanodine greatly decreased the amplitude (by 41%) and the frequency of EIDs by 36%. Ryanodine had no effect on electrically-evoked neurotransmitter release, paired-pulse facilitation, SEJP frequency, SEJP amplitude or SEJP amplitude distribution. These results show that activation of non-α7 nAChRs on sympathetic postganglionic nerve terminals induces high-amplitude junctional potentials that are argued to represent multipacketed neurotransmitter release synchronized by intraterminal Ca2+-induced Ca2+ release, triggered by Ca2+ influx directly through the nAChR. This nAChR-induced neurotransmitter release can be targeted pharmacologically without affecting spontaneous or electrically-evoked neurotransmitter release.